Adjuvant Therapy With Zoledronic Acid in Patients With Breast Cancer: A Systematic Review and Meta‐Analysis. (12th February 2013) - Valachis, Antonis; Polyzos, Nikolaos P.; Coleman, Robert E.; Gnant, Michael; Eidtmann, Holger; Brufsky, Adam M.; Aft, Rebecca; Tevaarwerk, Amye J.; Swenson, Karen; Lind, Pehr; Mauri, Davide
Abstract : Background: The purpose of the study was to estimate the impact on survival and fracture rates of the use of zoledronic acid versus no use (or delayed use) in the adjuvant treatment of patients with early‐stage (stages I–III) breast cancer. Materials and Methods: We performed a systematic review and meta‐analysis of randomized clinical trials. Trials were located through PubMed, ISI, Cochrane Library, and major cancer scientific meeting searches. All trials that randomized patients with primary breast cancer to undergo adjuvant treatment with zoledronic acid versus nonuse, placebo, or delayed use of zoledronic acid as treatment to individuals who develop osteoporosis were considered eligible. Standard meta‐analytic procedures were used to analyze the study outcomes. Results: Fifteen studies were considered eligible and were further analyzed. The use of zoledronic acid resulted in a statistically significant better overall survival outcome (five studies, 6, 414 patients; hazard ratio [HR], 0.81; 95% confidence interval [CI], 0.70–0.94). No significant differences were found for the disease‐free survival outcome (seven studies, 7, 541 patients; HR, 0.86; 95% CI, 0.70–1.06) or incidence of bone metastases (seven studies, 7, 543 patients; odds ratio [OR], 0.94; 95% CI, 0.64–1.37). Treatment with zoledronic acid led to a significantly lower overall fracture rate (OR, 0.78; 95% CI, 0.63–0.96). Finally, the rate of osteonecrosis of the jaw was 0.52%. Conclusion: Zoledronic acid as adjuvant therapy in breast cancer patients appears to not only reduce the fracture risk but also offer a survival benefit over placebo or no treatment. Abstract : A systematic review and meta‐analysis of randomized clinical trials estimating the impact on survival outcomes and fracture rates of the use of zoledronic acid versus no use (or delayed use) in the adjuvant treatment of early‐stage breast cancer patients is presented.